Alpine steppe plant communities of the Tibetan highlands - Miehe, Georg; Bach, Kerstin; Miehe, Sabine; Kluge, Jürgen; Yang, Yongping; La, Duo; Co, Sonam; Wesche, Karsten (Applied vegetation science, 2011)
Aim: To present a first description of plant communities of the Tibetan alpine steppes based on floristically complete vegetation records as a baseline reference for future ecological and palaeoecological studies. These constitute the world's largest alpine biome, but their vegetation is virtually unknown. Due to their vast extent, they are relevant for functioning of large-scale climatic systems. In turn, arid and alpine biomes are suspected to be highly sensitive to ongoing climate change, underwent climate-driven changes during the Last Glacial Maximum and have been subject to overgrazing and desertification. Location: Northwestern Tibetan highlands (China: Xizang, Qinghai), 4200 to 5400 m a.s.l., total area ca. 800 000 km2. Methods: Two hundred and fifty-three vegetation records with absolute percentage cover were classified based on expert knowledge and analysed by DCA; composition of plant functional types related to grazing resilience was also assessed. Results: Ten communities of alpine steppe were distinguished. A set of 11 alpine steppe species is distributed throughout the highlands, with a precipitation gradient between 350 mm yr-1 (southeast) and 20 to 50 mm yr-1 (northwest). The elevational range of more than 80% of species is larger than 1000 m. The data set comprises 30% endemic species, with ten endemic genera. Conclusions: The wide thermal and hygric range of many species and high rate of endemism do not support the idea of high sensitivity to climate change or occurrence of past climate-driven extinctions. The prevailing plant functional types are grazing resilient, and evidence for overgrazing is very limited. Cushion plants and dwarf shrubs, however, become increasingly rare around settlements, because they are uprooted for fuel. Hence, the world's largest arid alpine biome is apparently resilient to climatic changes and grazing. This contradicts common perceptions about arid and alpine ecosystems and therefore deserves intense multi-disciplinary research efforts.